2020
DOI: 10.21307/jofnem-2020-104
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing for taxonomic coverage: a comparison of methods to recover mesofauna from soil

Abstract: Manipulating soil properties to modify the dynamics between nematodes and their natural enemies has been proposed to conserve services such as the biological control of insect pests by entomopathogenic nematodes. Many soil microarthropods including acari mites and collembola are natural enemies of nematodes; however, little is known about the naturally occurring assemblages of these two soil dwelling groups and how they might be influenced by soil conditions. A method to efficiently recover both nematodes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Active methods such as the Baermann funnel and passive approaches such as filtering and flotation‐centrifugation are among the most recognized practices for sampling and extracting soil fauna, which are based on different physicochemical principles of soil fauna (Domingo‐Quero & Alonso‐Zarazaga, 2010). Dritsoulas and Duncan (2020) indicated that passive extraction methods consistently recovered significantly more soil microarthropods compared with the active techniques. This is in accordance with our findings since the ecological indices (abundance, richness and Shannon index) derived from the centrifugation method were constantly greater than the figures for the funnel techniques, though the differences were not always significant (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active methods such as the Baermann funnel and passive approaches such as filtering and flotation‐centrifugation are among the most recognized practices for sampling and extracting soil fauna, which are based on different physicochemical principles of soil fauna (Domingo‐Quero & Alonso‐Zarazaga, 2010). Dritsoulas and Duncan (2020) indicated that passive extraction methods consistently recovered significantly more soil microarthropods compared with the active techniques. This is in accordance with our findings since the ecological indices (abundance, richness and Shannon index) derived from the centrifugation method were constantly greater than the figures for the funnel techniques, though the differences were not always significant (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Soil mesofauna was extracted using two protocols: the heated funnel as described by Edwards (1991) and the modified centrifugal method (Dritsoulas & Duncan, 2020). For the funnel method, a thin layer of fine fresh soil (50 g per sample) was spread on a fine sieve or a small plastic basket and applied heat on top for 72 h. Under the effect of heat, soil mesofauna moved downward and was collected in the plastic tubes, which were tightly connected to funnels and filled with 70% alcohol.…”
Section: Soil and Root Sampling And Analysesmentioning
confidence: 99%
“…Sampling reliability/precision levels may be boosted and tailored with the current progress and advancements in processing PPN sampling rate [ 10 ] as well as PPN counting [ 12 ] to a several folds increase. Likewise, the extraction method chosen should provide the most authentic and relevant soil fauna/flora data [ 11 , 13 ]. Abd-Elgawad [ 11 ] presented tables to demonstrate considerably different funds needed to sample two nematode taxa with low and high action thresholds, root-knot nematodes (RKNs) on berseem clover and citrus nematodes on citrus trees, respectively, at various accuracy and precision levels.…”
Section: Sound Sampling and Extraction Methods As Prerequisites For T...mentioning
confidence: 99%
“…Baermann funnel method and its modifications can extract only live nematodes. Selecting a method may sometimes require further tests to find the most efficient extraction method of the existing fauna and flora related to IPM [ 15 ].…”
Section: Other Sampling and Extraction Methodsmentioning
confidence: 99%
“…Sucrose centrifugation is the most efficient method for microarthropod extraction. It is) used [ 15 ] as a model to study nematodes and their natural enemies such as collembolan and acari mites. Such techniques as species-specific primers and probes in quantitative polymerase chain reaction (qPCR) assessment, colony culture to count colony forming units per unit of root weight, sucrose centrifugation, Baermann funnel, sieving, or baiting with EPN-susceptible host may vary in the extraction efficiency [ 6 , 14 , 16 ].…”
Section: Ecological Considerations and Conceptsmentioning
confidence: 99%